Indoor environmental comfort in student hostel at Malaysia’s public university : a literature review - Yasmin AbdulJabbar Kareem Al-Taee,; Mohd Khairul Azhar Mat Sulaiman, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper aimed to review existing literature on student hostel building facilities and its room’s indoor environmental comfort condition in Malaysia’s public university. This study is structured by brief analysis on relevant studies located globally and subsequently, focusing more on studies located in Malaysia. An overview of the subject matter is presented to provide insight. These are supported by reviews of published papers from the last 15 years (2005-2020) in relevancy to the subject area which includes important sub-areas. The literature search was conducted via academic search engines such as Google Scholar, Taylor and Francis Online, ResearchGate, Emerald Insight, Academia, SpringerLink, and ScienceDirect. Terms relevant to the subject area such as “Student Hostel”, “Hostel”, “Hostel Facilities”, “Student Accommodation”, “University Accommodation” and “University Facilities” are used for the literature search using the academic search engine. In achieving a more accurate search specific to a University’s student accommodation (hostel building), a manual filtration was conducted to comb through the search results achieved from the academic search engines. The result of this literature review is a brief compilation of 18 global studies and focused on 29 studies in Malaysia, which are further classified/ grouped to form the structure of the paper. The review covers sub-areas such as building occupant’s indoor environment health-related issues, comfort, and satisfaction. This review is significant and necessary as its input function as a continuous monitoring study for this field, enriching the current body of knowledge and may be a point of reference for future studies.